The impact of surface acting and mindfulness on preschool teachers' burnout: the roles of emotional empathy and perceived organizational support - He, Yuanqing; Shuai, Chenghao; Gao, Shuyi; Guo, Baoqi; Li, Xiaowen (Frontiers in Psychology, 2025)
IntroductionPreschool teachers face significant occupational stress and emotional burdens, with burnout rates as high as 53.2% in China. Grounded in the Job Demands-Resources (JD-R) model and emotional labor theory, this study examines the interplay between surface acting (an emotion regulation strategy) and mindfulness (a psychological resource) in predicting burnout, while exploring emotional empathy as a mediator and perceived organizational support (POS) as a moderator.MethodsA three-wave longitudinal survey was conducted among 3,283 Chinese preschool teachers. Validated questionnaires measured surface acting, mindfulness, emotional empathy, POS, and burnout. Polynomial regression and response surface analysis were employed to analyze nonlinear interactions and mediation/moderation effects.ResultsThe interaction between surface acting and mindfulness significantly predicted burnout in a nonlinear pattern. Emotional empathy partially mediated this relationship, whereas POS moderated both direct and indirect effects. High POS buffered the negative impact of surface acting, particularly when mindfulness levels were low.ConclusionThe findings underscore the complex dynamics between emotion regulation strategies, personal resources, and organizational context in teacher wellbeing. Interventions such as mindfulness training and fostering supportive school environments may mitigate burnout among early childhood educators.